LSC 2016: from system approaches in lung disease to getting the job you want - Boots, Agnes; Flood, Emma; Kahn, Nicolas; Hardavella, Georgia; Bikov, Andras; Aamli, Ane; Skoczynski, Szymon (Breathe, 2016)
Tweetable abstract ERSpublications - click to tweetHighlights of the Lung Science Conference 2016 http://ow.ly/4nsKG2
Gesehen am 14.05.2020